A Bioecological Approach to the Life of a Child with Autism Spectrum Disorder - Münire Aydilek Çiftçi; Demet Vadi; İsmail Berat Uzun; Uğur Hassamancıoğlu (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: The aim of this study was to examine the lives of children with autism spectrum disorder from the perspective of the bioecological theory.Method: The research was designed as a descriptive phenomenological study focusing on the participants' descriptions and experiences of living with autism spectrum disorder. The starting point of descriptive phenomenology involves concrete descriptions of the events experienced by the participants from the perspective of their everyday life. Seventeen caregivers of children with autism spectrum disorder participated in the study. Semi-structured interview technique was used to collect the data.Findings: As a result of data analysis, the following sub-themes emerged: caregiver and child, other family members and child, immediate environment and child, teacher and child, the school in the microsystem; social field ties in the mesosystem; parent and teacher in the exosystem; the education system, support, community, laws, and communication tools in the macrosystem; and time and participation in the chronosystem.Discussion: When a child is diagnosed with autism spectrum disorder, the interactions of family members within themselves and with other people in society differ. Many factors such as the level of acceptance of the diagnosis of autism spectrum disorder by other individuals including parents and siblings, personality traits, and their opinions about autism spectrum disorder may have been determinant in interpersonal communication. The views on the teachers' approach can be explained by the education and personality traits of the teachers. In addition, variables such as the resources of the school or the level of acceptance of disability by the school staff may also have been effective in the results.Conclusion and Recommendations: Mothers were the primary caregivers of children, that the socioeconomic characteristics of parents and the personality traits of teachers affected children's development and education, and that the society was prejudiced and distant towards children due to lack of knowledge about children and the subject. It was expected that the quality and quantity of social awareness-raising activities would be improved. Parents who did not have sufficient financial income stated that they could not provide their children with the care and education they needed. It is believed that non-governmental organizations can help children with autism spectrum disorder access training and support in different disciplines such as sensory integration, sports activities, psychology, and nutrition.